The age of dualization : the changing face of inequality in deindustrializing societies - Emmenegger, Patrick (New York ; Oxford : Oxford University Press, 2012)
A landmark publication, this volume is geared for faculty and graduate students of economics, political science, social policy, and sociology, as well as policymakers concerned with increasing inequality in a period of deep economic and social crisis.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social stratification; Equality; Labor market; Deindustrialization